Could different direct restoration techniques affect interfacial gap and fracture resistance of endodontically treated anterior teeth? - Comba, Allegra; Baldi, Andrea; Saratti, Carlo Massimo; Rocca, Giovanni Tommaso; Torres, Carlos Rocha Gomes [UNESP]; Pereira, Gabriel Kalil Rocha; Valandro, Felipe Luiz; Scotti, Nicola (Springer Nature, 2021)
Objectives: To evaluate different direct restoration techniques on various cavity designs in anterior endodontically treated teeth (ETT). Materials and methods: Ninety upper central incisors (n = 90) were selected, endodontically treated, and divided into three groups (n = 30) accordingly to the cavity design: minimal endodontic cavity access (group A), endodontic access + mesial class III cavity (group B), and endodontic access + two class III cavities (group C). Three subgroups (n = 10) were then created accordingly to the restoration technique: nano hybrid composite restoration (subgroup a), glass fiber post + dual-cure luting cement (subgroup b), and bundled glass fiber + dual-cure luting cement (subgroup c). Samples underwent micro-CT scan, chewing simulation, and a second micro-CT scan. 3D quantification (mm3) of interfacial gap progression was performed; then, samples underwent fracture resistance test. Data were statistically analyzed setting significance at p < 0.05. Results: Groups A and B showed significantly lower interfacial gap progression compared with group C. Subgroup b performed significantly better compared with subgroups a and c. Improved fracture strength was reported for group C compared with group A, while both subgroups b and c performed better than subgroup a. Conclusions: Cavity design significantly influenced interfacial gap progression and fracture resistance. Fiber posts significantly lowered gap progression and improved fracture resistance while bundled fibers only increased fracture resistance. A significant reduction of non-repairable fractures was recorded when fibers were applied. Clinical relevance: A minimally invasive approach, conserving marginal crests, should be applied whenever possible. Inserting a fiber post is indicated when restoring anterior ETT, in order to reduce gap progression, improve fracture resistance, and avoid catastrophic failures.
Keywords: 3D interfacial gap; Endodontically treated teeth; Fracture pattern; Fracture resistance; Micro-CT; Post